Kepemimpinan Kepala Sekolah Dalam Membangun Profesionalitas Guru - Juwanto, Juwanto, Prof. Dr. Sutama, M.Pd, Dr. Samino,M.M (2015)
The purpose of this study was to describe the characteristics of curriculum and learning management in building the professionalism of teachers , school facilities and infrastructure management , education funds , and the management of the school environment. This research used a form of qualitative research using ethnographic research design. The data collection techniques that used are participant observation, in-depth interviews, and documentation. Data analysis techniques take place in the form of a cycle, i.e. grouping and sorting the data obtained from the study based on the quality and deduce the truth then describe the results to address existing problems. Results of this research is in the form of curriculum and learning management efforts in SMP Negeri 1 Terrace in the role of improving the professionalism of teachers with good infrastructure management, attention to the needs and interests of the learning infrastructure . Good educational fund management with the use of the allocation of funds for the purpose of conducting quality education . Environmental management education with the layout and the facilities good learning positive impact on the whole school community .